Restoring apoptosis dysregulation using survivin inhibitor in nasopharyngeal cancer. Issue 5 (11th January 2020) - Shi, Junli; Tan, Soo Yee; Lee, Andrea Zhe Ern; Zhang, Siting; Sasidharan, Swarnalatha Lucky; Wong, Benjamin; Tan, Min Han; Lim, Chwee Ming
Abstract: Background: Restoring apoptosis dysregulation via survivin inhibition has been investigated in several cancers. In Epstein‐Barr Virus (EBV)‐driven nasopharyngeal cancer (NPC), virally induced oncogenes can upregulate survivin. Therefore, we seek to investigate the therapeutic efficacy of YM‐155 (a survivin inhibitor) in NPC, both in vitro and in vivo models. Methods: Cytotoxicity, apoptosis, and active‐caspase 3 expression assays were performed. Results: Both NPC tissue and cells expressed high levels of survivin which were inhibited by YM‐155 in a dose‐dependent manner. In addition, YM‐155 induced apoptosis of NPC cells with an IC50 of 100 nM and inhibited tumor growth in vivo ( P < 0.05). YM‐155 in combination with cisplatin or radiation significantly increased overall cytotoxicity as compared to YM‐155 monotherapy. In the xenograft model, YM‐155 plus radiation additively achieved significantly higher percentage of active‐caspase 3‐positive tumor cells than radiation alone ( P  < 0.05). Conclusions: YM‐155 is a potential therapeutic agent for NPC through inhibiting survivin and restoring apoptosis dysregulation.